Sulfur-containing olefin elastomer composition and preparation method thereof
By combining modified bentonite and other components in sulfur-containing olefin elastomer materials, the problems of high cost of traditional flame retardants and environmental pollution are solved, and more efficient flame retardant performance and environmentally friendly production are achieved.
Patent Information
- Application Number
- CN202311384032.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-24
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing sulfur-containing olefin elastomer materials have poor flame retardant properties, and traditional flame retardants have problems such as high production costs, pollution of the ecological environment and complex manufacturing processes.
Composites such as hydroxyapatite, modified bentonite, pentaerythritol, melamine cyanurate/modified melamine cyanurate/melamine, coupling agent, flow modifier and light stabilizer are combined to form a sulfur-containing olefin elastomer composition with better flame retardant properties by plasma modification of bentonite.
The flame retardant properties of sulfur-containing olefin elastomer materials are significantly improved, production costs are reduced, manufacturing processes are simplified, and adverse effects on the environment and human health are reduced.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame retardancy, and in particular to a sulfur-containing olefin elastomer composition with flame retardancy and a preparation method thereof. Background Art
[0002] The chemical and petrochemical industries, due to the need to comprehensively utilize resources and develop new materials, need to improve the utilization rate of sulfur, especially the development of sulfur-containing or sulfur-rich organic polymers, and start relevant work; sulfur-containing polymers have also been used in environmental protection and restoration, infrared optics and new elastomer materials, antibacterial, and flame retardant. Among them, sulfur-containing olefin elastomer materials refer to elastomer materials that are polymerized by free radical addition reactions using elemental sulfur and olefins (monoolefins, dienes, cycloolefins) as raw materials. These polymers have SS bonds in their main chains, which can be reversibly broken and reorganized under certain conditions. These properties provide the possibility for thermally induced repair of these polymers and recycling of materials. Some of these properties are difficult to achieve with traditional polymer materials.
[0003] In practical applications, it is of great significance to improve and enhance the flame retardant properties of sulfur-containing olefin elastomer materials. The composite flame retardant materials with low cost, environmental protection requirements and good performance are compounded with sulfur-containing olefin elastomer materials to make composite flame retardant materials, which has broad prospects. However, some existing flame retardant materials have the problems of high synthesis cost, many products from chemical or petrochemical routes, complex ingredients (such as some compound organic compound flame retardants), and less than ideal environmental sustainability; some inorganic flame retardants have better flame retardant effects, but the addition amount is relatively large (30-50%), the dispersibility in polymer materials is not good, the processing process is more complicated, and the physical and mechanical properties of the materials are greatly affected.
[0004] Chinese patent CN201110106746.7 relates to a low-smoke halogen-free flame-retardant thermoplastic polyester elastomer and a preparation method thereof, which improves the anti-melting droplet performance of the thermoplastic polyester elastomer and improves the flame retardant grade. At the same time, the mechanical properties, heat resistance, heat aging resistance and water resistance are also relatively good. However, there are problems such as relatively high cost and unsatisfactory flame retardant effect in some applications.
[0005] Chinese patent CN201710259973.0 discloses a thermoplastic polyester elastomer flame retardant composition, which includes a thermoplastic polyester elastomer (TPEE) and a monomolecular expandable alkyl phosphinate flame retardant. Based on 100 parts by mass of the TPEE flame retardant composition, the monomolecular expandable alkyl phosphinate is 10 to 40 parts by mass, and the rest is TPEE. The monomolecular expandable alkyl phosphinate is a monomolecular expandable alkyl phosphinate metal salt that integrates an acid source, a carbon source, and a gas source, and the monomolecular expandable alkyl phosphinate contains a carboxylate structure that can produce good compatibility with TPEE. However, there may be problems such as relatively unsatisfactory flame retardant and heat insulation effects and insufficient residual carbon.
[0006] Chinese patent CN201611128268.9 compounds expandable graphite, fly ash, polyether polyol, and isocyanate, adds a foaming agent and polydimethylsiloxane and / or silicone oil as a foam stabilizer, and prepares a flame retardant polyurethane foam.
[0007] Chinese patent CN107778638A discloses a halogen-free flame-retardant ultra-high molecular weight polyethylene material and a preparation method thereof, using the following raw materials: ultra-high molecular weight polyethylene substrate, pyro (poly) phosphate piperazine, alkyl hypophosphite, coupling agent, light stabilizer, plasticizer, flow modifier and organic modified nano-scale inorganic filler. The flame-retardant ultra-high molecular weight polyethylene material prepared by the invention does not contain halogen, but the production cost is relatively high.
[0008] Chinese patent CN 101948581 A discloses an intumescent flame-retardant polyethylene containing an organosilicon compound, wherein the intumescent flame-retardant polyethylene containing an organosilicon compound also contains a metal oxide hydrate of an organosilicon flame retardant synergist, and the contents of each component by weight percentage are: polyethylene 70-80%, compound intumescent flame retardant 17-29.5%, and metal oxide hydrate containing an organosilicon flame retardant synergist 0.5-3%, but the process is relatively complicated.
[0009] Chinese patent CN111647265A discloses an oil-resistant, low-smoke, halogen-free, flame-retardant flexible polyurethane cable material and its preparation method, which is composed of the following raw materials in parts by weight: 30-40 parts of thermoplastic polyurethane elastomer, 7-10 parts of polar rubber, 10-15 parts of EPDM rubber, 5-8 parts of polymer compatibilizer, 5-8 parts of terminal isocyanate polyurethane prepolymer, 80-100 parts of inorganic flame retardant, 5-8 parts of phosphorus flame retardant, 14-20 parts of white carbon black, 5-15 parts of mineral filler, 3-7 parts of vulcanization accelerator, 0.5-3 parts of radiation sensitizer, 3-5 parts of antioxidant, 0.2-1.5 parts of coupling agent, 1-2 parts of antistatic agent, and 1-2 parts of calcium stearate. However, this method forms functional inorganic particles with polyurethane as soft shell and filler as hard core through mechanochemical reaction, and the process is relatively complicated.
[0010] Chinese patent CN103834107A discloses a modified lignin expansion flame retardant TPO composite material and its preparation method and application. The composite material is composed of the following components by mass percentage: 60-80% thermoplastic polyolefin elastomer, 3-8% modified wood, 10-30% ammonium polyphosphate, and 1-8% melamine cyanurate. However, the method relates to a flame retardant TPO composite material, and does not relate to a sulfur-containing olefin elastomer composition.
[0011] The flame retardant properties of existing sulfur-containing olefin elastomer materials are relatively poor, and there is an urgent need to increase the added value of the materials and develop an environmentally friendly, novel flame retardant sulfur-containing olefin elastomer material to broaden the application areas of the products and continuously meet market demand. Summary of the invention
[0012] The purpose of the present invention is to develop a more environmentally friendly and effective halogen-free green flame retardant, to increase the added value of sulfur-containing olefin elastomer materials, to solve some problems existing in the current flame retardant system, such as high production cost, pollution of the ecological environment, and complex manufacturing process, and to make full use of natural materials and industrial waste, to reduce the production cost of flame retardants and the adverse effects of polymer materials on the environment and human health when burned.
[0013] To achieve the above-mentioned purpose, the present invention provides a sulfur-containing olefin elastomer composition, which comprises the following components in parts by mass: 10-15 parts of hydroxyapatite, 11-18 parts of modified bentonite, 3-11 parts of pentaerythritol, 8-12 parts of at least one of melamine cyanurate, modified melamine cyanurate and melamine, 0.5-1 part of a coupling agent, 1-5.5 parts of a flow modifier, 0.5-3 parts of a light stabilizer, and 90-140 parts of a sulfur-containing olefin elastomer material base material.
[0014] In the sulfur-containing olefin elastomer composition of the present invention, at least one of melamine cyanurate, modified melamine cyanurate and melamine refers to adding one of them, or adding two of them, or adding all three of them at the same time; specifically, the melamine cyanurate, modified melamine cyanurate and melamine can be added alone, or melamine cyanurate and modified melamine cyanurate can be added, or modified melamine cyanurate and melamine can be added, or melamine cyanurate and melamine can be added, and further, melamine cyanurate, modified melamine cyanurate and melamine can be added at the same time.
[0015] The modified melamine cyanurate of the present invention refers to melamine cyanurate modified by a compounding agent and a heat stabilizer, or modified by a conventional method. The present invention does not particularly limit the modification process of the modified melamine cyanurate. In some embodiments, it can be prepared by the method disclosed in CN106700130A and CN10453078A.
[0016] The sulfur-containing olefin elastomer composition of the present invention comprises: 10-11 parts of hydroxyapatite, 11-13 parts of modified bentonite, 7-9 parts of pentaerythritol, 10-12 parts of at least one of melamine cyanurate, modified melamine cyanurate and melamine, 0.7-0.9 parts of coupling agent, 1-3.5 parts of flow modifier, 0.8-2 parts of light stabilizer and 100-130 parts of sulfur-containing olefin elastomer material base material.
[0017] The sulfur-containing olefin elastomer composition of the present invention, the modified bentonite is bentonite that has been subjected to plasma modification treatment.
[0018] The sulfur-containing olefin elastomer composition of the present invention is prepared by the following steps: adding bentonite to a plasma reactor, inputting a treatment gas, and treating the bentonite by using electrons, free radicals, ions, and molecules in an excited state in the plasma reactor to obtain the modified bentonite.
[0019] The sulfur-containing olefin elastomer composition of the present invention, the processing gas includes but is not limited to at least one of oxygen, nitrogen, argon and methane.
[0020] The sulfur-containing olefin elastomer composition of the present invention has a plasma reactor with a power of 30-100 watts, a treatment time of 10-50 minutes, and a treatment gas flow rate of 20-60 ml / min.
[0021] After being modified by gas, the surface of bentonite is rich in active groups such as hydroxyl and carbonyl, which can improve the surface performance and activity of bentonite, enable it to react better with other substances, and promote better combination of flame retardants and sulfur-containing olefin elastomer material base materials, so as to achieve the purpose of improving flame retardant effect. Compared with other bentonite modification technologies, such as organic modification, acid modification, and ion exchange modification, no chemicals are added in the entire treatment process, and there is no solvent residue afterwards. The overall process is simple and easy.
[0022] In the sulfur-containing olefin elastomer composition of the present invention, the coupling agent includes but is not limited to one of titanates and aluminates.
[0023] The silane coupling agent is, for example but not limited to, at least one of vinyltrichlorosilane, vinyltrimethoxysilane, vinylmethyldichlorosilane, γ-chloropropyltrimethoxysilane, γ-chloropropyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, and γ-aminoethylaminopropyltrimethoxysilane.
[0024] The titanate coupling agent is, for example but not limited to, at least one of bis(dioctyl pyrophosphate)ethylene titanate, isopropyl tri(isostearoyl) titanate, isopropyl tri(dioctyl pyrophosphate) titanate, isopropyl di(methacryloyl) isostearyl titanate, and isopropyl tri(dodecylbenzenesulfonyl) titanate.
[0025] The aluminate coupling agent is, for example but not limited to, at least one of isopropyl distearate acyloxyaluminate, trimethyl aluminate, triethyl aluminate, and tribenzyl aluminate.
[0026] The sulfur-containing olefin elastomer composition of the present invention, the flow improver includes but is not limited to at least one of polyethylene wax, low-density polyethylene and modified polyethylene wax.
[0027] The sulfur-containing olefin elastomer composition of the present invention, wherein the light stabilizer includes but is not limited to at least one of a benzotriazole light stabilizer, a benzophenone light stabilizer and a triazine light stabilizer.
[0028] The benzotriazole light stabilizer is, for example but not limited to, at least one of 2'-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, and 2-(2'-hydroxy-3',5'-di-tert-amylphenylbenzotriazole.
[0029] The benzophenone light stabilizer is, for example but not limited to, 2-hydroxy-4-n-octyloxybenzophenone.
[0030] The triazine light stabilizer is, for example but not limited to, 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl)-5-octyloxyphenol.
[0031] The sulfur-containing olefin elastomer composition of the present invention is not particularly limited to the type or performance of the sulfur-containing olefin elastomer base material, which can be selected according to conventional methods in the art. The weight average molecular weight of the sulfur-containing olefin elastomer base material can be, for example but not limited to, 6000-450000 g / mol.
[0032] The sulfur-containing olefin elastomer composition of the present invention further comprises an antioxidant, and the antioxidant is added in an amount of 0.1-3 parts by weight, preferably 0.3-2 parts by weight.
[0033] The present invention does not particularly limit the type of antioxidant, and the antioxidant is, for example but not limited to, selected from antioxidant 1010, antioxidant 1076, antioxidant 168, antioxidant 626, and compound antioxidants thereof.
[0034] Preferably, the antioxidant is a composite antioxidant, the main antioxidant of the composite antioxidant is antioxidant 1010 or antioxidant 1076, and the auxiliary antioxidant is antioxidant 168 or antioxidant 626; wherein the mass ratio of the main antioxidant to the auxiliary antioxidant is 1:1-1:2, and the mass ratio is, for example but not limited to, 1:1, 1:1.5, 1:2.
[0035] The present invention also discloses a method for preparing the sulfur-containing olefin elastomer composition, which comprises the following steps:
[0036] Step 1: mixing hydroxyapatite, modified bentonite, pentaerythritol, at least one of melamine cyanurate, modified melamine cyanurate, melamine, and a coupling agent to obtain a composite flame retardant material matrix;
[0037] Step 2: Add the compounded flame retardant material matrix, flow modifier, light stabilizer, and sulfur-containing olefin elastomer material base into an extruder for mixing, and obtain the sulfur-containing olefin elastomer composition after extrusion.
[0038] The preparation method of the sulfur-containing olefin elastomer composition of the present invention can also be described in detail as follows:
[0039] Step 1, preparation of modified bentonite:
[0040] Using a plasma reactor, at a certain power and treatment time, oxygen, nitrogen, argon or methane is used as the treatment gas, and active particles such as electrons, free radicals, ions, and excited molecules in the plasma are used to treat bentonite for a certain period of time to obtain modified bentonite. The power of the plasma reactor is generally 30-100 watts, the treatment time is 10-50 minutes, and the gas flow rate is 20-60 ml / minute.
[0041] Step 2: Compounding of modified bentonite and other flame retardants:
[0042] The modified bentonite (11-18 parts by mass) obtained in step 1 is mixed with hydroxyapatite (10-15 parts by mass), melamine cyanurate, modified melamine cyanurate, at least one of melamine (8-12 parts by mass), pentaerythritol (3-11 parts by mass), and a coupling agent (0.5-1 parts by mass) to form a composite flame retardant material matrix.
[0043] Step 3, blending of the compounded flame retardant material matrix and the sulfur-containing olefin elastomer material base material:
[0044] The composite flame retardant material matrix obtained in step 2 is added into a twin-screw extruder at a certain temperature for mixing with a flow modifier (1-5.5 parts by mass), a light stabilizer (0.5-3 parts by mass), a sulfur-containing olefin elastomer base material (90-140 parts by mass), and an antioxidant (0.1-3 parts by mass), and extruded to obtain a sulfur-containing olefin elastomer composition.
[0045] The present invention makes extensive use of cheap bentonite, has obvious environmental value, and can greatly reduce the production cost of the flame-retardant sulfur-containing olefin elastomer composition. The bentonite can be bentonite that has been simply treated and discarded after industrial use. The preparation method of the present invention effectively reduces the overall production cost of the flame retardant, the preparation process is simple and easy, and is green and environmentally friendly. The raw materials do not contain halogens, which is more green and environmentally friendly; it also reduces the adverse effects of the burning materials on the environment and human body. The present invention modifies bentonite through plasma, and the surface of the modified bentonite has relatively abundant active groups such as hydroxyl and carbonyl, which is conducive to the subsequent formation of the sulfur-containing olefin elastomer composition, and improves the flame retardant properties of the sulfur-containing olefin elastomer composition. Compared with other existing modification technologies such as organic modified bentonite and acid modified bentonite, it has the characteristics of being more environmentally friendly and efficient. The present invention compounds hydroxyapatite, modified bentonite, pentaerythritol, melamine cyanurate / modified melamine cyanurate / melamine, and simultaneously adds a coupling agent, a flow modifier, a light stabilizer, a sulfur-containing olefin elastomer material base and other components to modify and form a sulfur-containing olefin elastomer composition. The components act synergistically, and the heat resistance and flame retardancy of the obtained sulfur-containing olefin elastomer composition are also improved, and the generation of molten droplets is effectively suppressed. 。 DETAILED DESCRIPTION
[0046] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention. The raw materials used in the following examples and comparative examples, unless otherwise specified, are all commercially available.
[0047] Analytical methods
[0048] The limiting oxygen index (LOI) was tested using a LOI instrument (Model 5801, produced by Kunshan Yangyi Testing Instrument Co., Ltd.) using the standard GB / T 2406-2009.
[0049] Raw materials and sources
[0050] Bentonite, with an active ingredient content of 98% and a mesh size of 300, was purchased from Haoyuan Bentonite Factory in Fangzi District, Weifang City; hydroxyapatite, with an active ingredient content of 99%, was purchased from Wuhan Chengtian Fine Chemical Co., Ltd., an industrial product; melamine cyanurate was purchased from Shandong Dongxin Holding Group Co., Ltd. with a purity of 99%; modified melamine cyanurate was homemade; melamine was purchased from Shandong Juchuan Chemical Co., Ltd., an industrial product with a purity of 99%; pentaerythritol was purchased from Shandong Shouhua Chemical Co., Ltd.; titanate coupling agents and aluminate coupling agents were commercially available, industrial products; light stabilizers were commercially available, industrial products; antioxidants 1010, 1076, 168, and 626 were purchased from Yingkou Fengguang Chemical Co., Ltd.
[0051] Example 1
[0052] (1) Preparation of modified bentonite:
[0053] A plasma reactor was used, oxygen was used as a processing gas; the reaction power was 60 watts, the processing time was 40 minutes, and the gas flow rate was 40 ml / minute to modify the bentonite to obtain modified bentonite.
[0054] (2) Compounding of modified bentonite and other flame retardants:
[0055] 15 parts by mass of the modified bentonite obtained in step (1) are mixed with 12 parts by mass of hydroxyapatite, 11 parts by mass of melamine cyanurate, 8 parts by mass of pentaerythritol, and 0.7 parts by mass of a titanate coupling agent, bis(dioctyloxypyrophosphate)ethylene titanate, to obtain a composite flame retardant material matrix.
[0056] (3) Blending of compounded flame retardant material matrix and sulfur-containing olefin elastomer:
[0057] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 215° C. for granulation with 2.5 parts by mass of polyethylene wax as a flow modifier, 1.5 parts by mass of benzotriazole 2'-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole as a light stabilizer, 115 parts by mass of a sulfur-containing olefin elastomer base material, and 0.3 parts by mass of an antioxidant having a ratio of 1:2 between antioxidant 1010 and antioxidant 168, to obtain a flame retardant sulfur-containing olefin elastomer composition.
[0058] The limiting oxygen index (LOI) of the obtained sulfur-containing olefin elastomer composition was 28.
[0059] Example 2
[0060] (1) Preparation of modified bentonite:
[0061] A plasma reactor was used, nitrogen was used as the processing gas; the reaction power was 50 watts, the processing time was 45 minutes, and the gas flow rate was 45 ml / minute to modify the bentonite to obtain modified bentonite.
[0062] (2) Compounding of modified bentonite and other flame retardants:
[0063] 11 parts by mass of the modified bentonite obtained in step (1) are mixed with 12 parts by mass of hydroxyapatite, 12 parts by mass of melamine, 9 parts by mass of pentaerythritol, and 0.8 parts by mass of a titanate coupling agent, isopropyl tri(dodecylbenzenesulfonyl) titanate, to obtain a composite flame retardant material matrix.
[0064] (3) Blending of compounded flame retardant material matrix and sulfur-containing olefin elastomer base material:
[0065] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 220° C. for granulation to obtain a sulfur-containing olefin elastomer composition, wherein 140 parts by mass of a sulfur-containing olefin elastomer base material, 5 parts by mass of a flow modifier polyethylene wax, 1.5 parts by mass of a light stabilizer benzotriazole 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, and 0.3 parts by mass of a composite antioxidant formed by an antioxidant 1010 and an antioxidant 626 in a mass ratio of 1:2.
[0066] The limiting oxygen index (LOI) of the obtained sulfur-containing olefin elastomer composition was 29.
[0067] Example 3
[0068] (1) Preparation of modified bentonite:
[0069] A plasma reactor was used, methane gas was used as the processing gas; the reaction power was 60 watts, the processing time was 50 minutes, and the gas flow rate was 55 ml / minute to modify the bentonite to obtain modified bentonite.
[0070] (2) Compounding of modified bentonite and other flame retardants:
[0071] 15 parts by mass of the modified bentonite obtained in step (1) are mixed with 10 parts by mass of hydroxyapatite, 8 parts by mass of melamine cyanurate, 10 parts by mass of pentaerythritol, and 0.6 parts by mass of triethyl aluminate, an aluminate coupling agent, to obtain a composite flame retardant material matrix.
[0072] (3) Blending of compounded flame retardant material matrix and sulfur-containing olefin elastomer:
[0073] The composite flame retardant material matrix obtained in step (2) and 5 parts by mass of polyethylene wax as a flow modifier, 1.4 parts by mass of benzotriazole 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole as a light stabilizer, 120 parts by mass of a sulfur-containing olefin elastomer base material, and 0.3 parts by mass of a composite antioxidant formed by antioxidant 1076 and antioxidant 626 in a mass ratio of 1:1.5 are added into a twin-screw extruder at 225° C. for granulation to obtain a sulfur-containing olefin elastomer composition.
[0074] The limiting oxygen index (LOI) of the obtained sulfur-containing olefin elastomer composition was 28.
[0075] Example 4
[0076] (1) Preparation of modified bentonite:
[0077] A plasma reactor was used, nitrogen was used as the processing gas; the reaction power was 65 watts, the processing time was 45 minutes, and the gas flow rate was 60 ml / minute to modify the bentonite to obtain modified bentonite.
[0078] (2) Compounding of modified bentonite and other flame retardants:
[0079] 13 parts by mass of the modified bentonite obtained in step (1) are mixed with 12 parts by mass of hydroxyapatite, 11 parts by mass of melamine phosphate, 5 parts by mass of pentaerythritol, and 0.7 parts by mass of an aluminate coupling agent isopropyl distearate acyloxyaluminate to obtain a composite flame retardant material matrix.
[0080] (3) Blending of compounded flame retardant material matrix and sulfur-containing olefin elastomer:
[0081] The composite flame retardant material matrix obtained in step (2) and 4.5 parts by mass of low-density polyethylene as a flow modifier, 1.5 parts by mass of benzophenone 2-hydroxy-4-octyloxybenzophenone as a light stabilizer, 130 parts by mass of a sulfur-containing olefin elastomer base material, and 0.3 parts by mass of a composite antioxidant formed by antioxidant 1076 and antioxidant 626 in a mass ratio of 1:1.5 are added into a twin-screw extruder at 220° C. for granulation to obtain a sulfur-containing olefin elastomer composition.
[0082] The limiting oxygen index (LOI) of the obtained sulfur-containing olefin elastomer composition was 30.
[0083] Example 5
[0084] (1) Preparation of modified bentonite:
[0085] A plasma reactor was used, argon gas was used as the processing gas; the reaction power was 55 watts, the processing time was 40 minutes, and the gas flow rate was 60 ml / minute to modify the bentonite to obtain modified bentonite.
[0086] (2) Compounding of modified bentonite and other flame retardants:
[0087] 15 parts by mass of the modified bentonite obtained in step (1) are mixed with 13 parts by mass of hydroxyapatite, 9 parts by mass of melamine phosphate, 10 parts by mass of pentaerythritol, and 0.7 parts by mass of a titanate coupling agent, bis(dioctyloxypyrophosphate)ethylene titanate, to obtain a composite flame retardant material matrix.
[0088] (3) Blending of compounded flame retardant material matrix and sulfur-containing olefin elastomer:
[0089] The composite flame retardant material matrix obtained in step (2) and 4 parts by mass of low-density polyethylene as a flow modifier, 1 part by mass of benzophenone 2-hydroxy-4-octyloxybenzophenone as a light stabilizer, 100 parts by mass of a sulfur-containing olefin elastomer base material, and 0.3 parts by mass of a composite antioxidant formed by antioxidant 1076 and antioxidant 168 in a mass ratio of 1:1.5 are added into a twin-screw extruder at 230° C. for granulation to obtain a sulfur-containing olefin elastomer composition.
[0090] The limiting oxygen index (LOI) of the obtained sulfur-containing olefin elastomer composition was 29.
[0091] Example 6
[0092] (1) Preparation of modified bentonite:
[0093] A plasma reactor was used, nitrogen was used as the processing gas; the reaction power was 70 watts, the processing time was 50 minutes, and the gas flow rate was 50 ml / minute to modify the bentonite to obtain modified bentonite.
[0094] (2) Compounding of modified bentonite and other flame retardants:
[0095] 14 parts by mass of the modified bentonite obtained in step (1) are mixed with 13 parts by mass of hydroxyapatite, 12 parts by mass of modified melamine cyanurate, 5 parts by mass of pentaerythritol, and 0.8 parts by mass of a silane coupling agent γ-mercaptopropyltriethoxysilane to obtain a composite flame retardant material matrix.
[0096] (3) Blending of compounded flame retardant material matrix and sulfur-containing olefin elastomer:
[0097] The composite flame retardant material matrix obtained in step (2) and 3.5 parts by mass of flow modifier modified polyethylene wax, 1.6 parts by mass of light stabilizer benzotriazole 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 135 parts by mass of sulfur-containing olefin elastomer base material, and 0.3 parts by mass of a composite antioxidant formed by antioxidant 1010 and antioxidant 168 in a mass ratio of 1:2 are added into a twin-screw extruder at 215° C. for granulation to obtain a sulfur-containing olefin elastomer composition.
[0098] The limiting oxygen index (LOI) of the obtained sulfur-containing olefin elastomer composition was 31.
[0099] Example 7
[0100] (1) Preparation of modified bentonite:
[0101] A plasma reactor was used, oxygen was used as a processing gas, the reaction power was 70 watts, the processing time was 35 minutes, and the gas flow rate was 60 ml / minute to modify the bentonite to obtain modified bentonite.
[0102] (2) Compounding of modified bentonite and other flame retardants:
[0103] 11 parts by mass of the modified bentonite obtained in step (1) are mixed with 15 parts by mass of hydroxyapatite, 10 parts by mass of melamine, 7 parts by mass of pentaerythritol, and 0.7 parts by mass of trimethyl aluminate, an aluminate coupling agent, to obtain a composite flame retardant material matrix.
[0104] (3) Blending of compounded flame retardant material matrix and sulfur-containing olefin elastomer:
[0105] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 225° C. for granulation, and 5.5 parts by mass of a flow modifier modified polyethylene wax, 1.5 parts by mass of a light stabilizer benzophenone 2-hydroxy-4-octyloxybenzophenone, 90 parts by mass of a sulfur-containing olefin elastomer base material, and 0.3 parts by mass of a composite antioxidant formed by an antioxidant 1010 and an antioxidant 626 in a mass ratio of 1:1.5 are added to the mixture to obtain a sulfur-containing olefin elastomer composition.
[0106] The limiting oxygen index (LOI) of the obtained sulfur-containing olefin elastomer composition was 30.
[0107] Example 8
[0108] (1) Preparation of modified bentonite:
[0109] A plasma reactor was used, oxygen was used as a processing gas, the reaction power was 75 watts, the processing time was 45 minutes, and the gas flow rate was 45 ml / minute to modify the bentonite to obtain modified bentonite.
[0110] (2) Compounding of modified bentonite and other flame retardants:
[0111] 12 parts by mass of the modified bentonite obtained in step (1) are mixed with 12 parts by mass of hydroxyapatite, 8 parts by mass of melamine, 9 parts by mass of pentaerythritol, and 0.7 parts by mass of an aluminate coupling agent, isopropyl distearate acyloxyaluminate, to obtain a composite flame retardant material matrix.
[0112] (3) Blending of compounded flame retardant material matrix and sulfur-containing olefin elastomer:
[0113] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 225° C. for granulation, and a sulfur-containing olefin elastomer composition is obtained by adding 5.5 parts by mass of a flow modifier modified polyethylene wax, 1.6 parts by mass of a light stabilizer benzophenone 2-hydroxy-4-n-octyloxybenzophenone, 125 parts by mass of a sulfur-containing olefin elastomer base material, and 0.3 parts by mass of a composite antioxidant formed by an antioxidant 1010 and an antioxidant 626 in a mass ratio of 1:1.5.
[0114] The limiting oxygen index (LOI) of the obtained sulfur-containing olefin elastomer composition was 29.
[0115] Example 9
[0116] (1) Preparation of modified bentonite:
[0117] A plasma reactor was used, oxygen was used as a processing gas, the reaction power was 70 watts, the processing time was 50 minutes, and the gas flow rate was 45 ml / minute to modify the bentonite to obtain modified bentonite.
[0118] (2) Compounding of modified bentonite and other flame retardants:
[0119] 12 parts by mass of the modified bentonite obtained in step (1) are mixed with 13 parts by mass of hydroxyapatite, 10 parts by mass of melamine, 9 parts by mass of pentaerythritol, and 0.6 parts by mass of triethyl aluminate, an aluminate coupling agent, to obtain a composite flame retardant material matrix.
[0120] (3) Blending of compounded flame retardant material matrix and sulfur-containing olefin elastomer:
[0121] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 225° C. for granulation, and a sulfur-containing olefin elastomer composition is obtained, wherein 5 parts by mass of a flow modifier modified polyethylene wax, 2.8 parts by mass of a light stabilizer benzophenone, 130 parts by mass of a sulfur-containing olefin elastomer base material, and 0.3 parts by mass of an antioxidant having a ratio of 1:2 between antioxidant 1076 and antioxidant 168.
[0122] The limiting oxygen index (LOI) of the obtained sulfur-containing olefin elastomer composition was 30.
[0123] Example 10
[0124] (1) Preparation of modified bentonite:
[0125] A plasma reactor was used, oxygen was used as a processing gas; the reaction power was 60 watts, the processing time was 40 minutes, and the gas flow rate was 40 ml / minute to modify the bentonite to obtain modified bentonite.
[0126] (2) Compounding of modified bentonite and other flame retardants:
[0127] 13 parts by mass of the modified bentonite obtained in step (1) are mixed with 12 parts by mass of hydroxyapatite, 4 parts by mass of melamine cyanurate, 6 parts by mass of modified melamine cyanurate, 8 parts by mass of pentaerythritol, and 0.5 parts by mass of a titanate coupling agent, bis(dioctylpyrophosphate)ethylene titanate, to obtain a composite flame retardant material matrix.
[0128] (3) Blending of compounded flame retardant material matrix and sulfur-containing olefin elastomer:
[0129] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 215° C. for granulation, and 1 part by mass of a flow modifier polyethylene wax, 0.9 part by mass of a light stabilizer benzotriazole 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 115 parts by mass of a sulfur-containing olefin elastomer base material, and 0.3 part by mass of an antioxidant in a ratio of 1:2 of an antioxidant 1076 and an antioxidant 626 to obtain a flame retardant sulfur-containing olefin elastomer composition.
[0130] The limiting oxygen index (LOI) of the obtained sulfur-containing olefin elastomer composition was 30.
[0131] Embodiment 11
[0132] (1) Preparation of modified bentonite:
[0133] A plasma reactor was used, oxygen was used as a processing gas; the reaction power was 60 watts, the processing time was 40 minutes, and the gas flow rate was 40 ml / minute to modify the bentonite to obtain modified bentonite.
[0134] (2) Compounding of modified bentonite and other flame retardants:
[0135] 13 parts by mass of the modified bentonite obtained in step (1) are mixed with 12 parts by mass of hydroxyapatite, 4 parts by mass of melamine cyanurate, 6 parts by mass of modified melamine cyanurate, 8 parts by mass of pentaerythritol, and 0.5 parts by mass of a titanate coupling agent, bis(dioctylpyrophosphate)ethylene titanate, to obtain a composite flame retardant material matrix.
[0136] (3) Blending of compounded flame retardant material matrix and sulfur-containing olefin elastomer:
[0137] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 215° C. for granulation with 1 part by mass of a flow modifier polyethylene wax, 0.9 part by mass of a light stabilizer benzotriazole 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 115 parts by mass of a sulfur-containing olefin elastomer base material, and 0.3 parts by mass of an antioxidant 1076 to obtain a flame retardant sulfur-containing olefin elastomer composition.
[0138] The limiting oxygen index (LOI) of the obtained sulfur-containing olefin elastomer composition was 27.
[0139] Example 12
[0140] (1) Preparation of modified bentonite:
[0141] A plasma reactor was used, oxygen was used as a processing gas; the reaction power was 60 watts, the processing time was 40 minutes, and the gas flow rate was 40 ml / minute to modify the bentonite to obtain modified bentonite.
[0142] (2) Compounding of modified bentonite and other flame retardants:
[0143] 13 parts by mass of the modified bentonite obtained in step (1) are mixed with 12 parts by mass of hydroxyapatite, 4 parts by mass of melamine cyanurate, 6 parts by mass of modified melamine cyanurate, 8 parts by mass of pentaerythritol, and 0.5 parts by mass of a titanate coupling agent, bis(dioctylpyrophosphate)ethylene titanate, to obtain a composite flame retardant material matrix.
[0144] (3) Blending of compounded flame retardant material matrix and sulfur-containing olefin elastomer:
[0145] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 215° C. for granulation with 1 part by mass of a flow modifier polyethylene wax, 0.9 part by mass of a light stabilizer benzotriazole 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, and 115 parts by mass of a sulfur-containing olefin elastomer base material to obtain a flame retardant sulfur-containing olefin elastomer composition.
[0146] The limiting oxygen index (LOI) of the obtained sulfur-containing olefin elastomer composition was 26.
[0147] Embodiment 13
[0148] (1) Preparation of modified bentonite:
[0149] A plasma reactor was used, oxygen was used as a processing gas; the reaction power was 60 watts, the processing time was 40 minutes, and the gas flow rate was 40 ml / minute to modify the bentonite to obtain modified bentonite.
[0150] (2) Compounding of modified bentonite and other flame retardants:
[0151] 15 parts by mass of the modified bentonite obtained in step (1) are mixed with 12 parts by mass of hydroxyapatite, 3 parts by mass of melamine cyanurate, 3 parts by mass of modified melamine cyanurate, 4 parts by mass of melamine, 8 parts by mass of pentaerythritol, and 1 part by mass of a titanate coupling agent, bis(dioctylpyrophosphate)ethylene titanate, to obtain a composite flame retardant material matrix.
[0152] (3) Blending of compounded flame retardant material matrix and sulfur-containing olefin elastomer:
[0153] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 215° C. for granulation with 2.5 parts by mass of polyethylene wax as a flow modifier, 2 parts by mass of benzotriazole 2'-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole as a light stabilizer, 115 parts by mass of a sulfur-containing olefin elastomer base material, and 0.3 parts by mass of an antioxidant having a ratio of 1:2 between antioxidant 1010 and antioxidant 168, to obtain a flame retardant sulfur-containing olefin elastomer composition.
[0154] The limiting oxygen index (LOI) of the obtained sulfur-containing olefin elastomer composition was 29.
[0155] Comparative Example 1
[0156] The difference from Example 8 is that melamine is not added.
[0157] (1) Preparation of modified bentonite:
[0158] A plasma reactor was used, oxygen was used as a processing gas, the reaction power was 75 watts, the processing time was 45 minutes, and the gas flow rate was 45 ml / minute to modify the bentonite to obtain modified bentonite.
[0159] (2) Compounding of modified bentonite and other flame retardants:
[0160] 12 parts by mass of the modified bentonite obtained in step (1) are mixed with 12 parts by mass of hydroxyapatite, 9 parts by mass of pentaerythritol, and 0.7 parts by mass of an aluminate coupling agent, isopropyl distearate acyloxyaluminate, to obtain a composite flame retardant material matrix.
[0161] (3) Blending of compounded flame retardant material matrix and sulfur-containing olefin elastomer:
[0162] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 225° C. for granulation, and 5.5 parts by mass of flow modifier modified polyethylene wax, 1.6 parts by mass of light stabilizer 2-hydroxy-4-n-octyloxybenzophenone, 125 parts by mass of sulfur-containing olefin elastomer base material, and 0.3 parts by mass of a composite antioxidant formed by antioxidant 1010 and antioxidant 626 in a mass ratio of 1:1.5 are obtained.
[0163] The limiting oxygen index (LOI) of the obtained sulfur-containing olefin elastomer composition was 25.
[0164] Comparative Example 2
[0165] The difference from Example 8 is that pentaerythritol is not added.
[0166] (1) Preparation of modified bentonite:
[0167] A plasma reactor was used, oxygen was used as a processing gas, the reaction power was 75 watts, the processing time was 45 minutes, and the gas flow rate was 45 ml / minute to modify the bentonite to obtain modified bentonite.
[0168] (2) Compounding of modified bentonite and other flame retardants:
[0169] 12 parts by mass of the modified bentonite obtained in step (1) are mixed with 12 parts by mass of hydroxyapatite, 8 parts by mass of melamine, and 0.7 parts by mass of an aluminate coupling agent, isopropyl distearate acyloxyaluminate, to obtain a composite flame retardant material matrix.
[0170] (3) Blending of compounded flame retardant material matrix and sulfur-containing olefin elastomer:
[0171] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 225° C. for granulation, and 5.5 parts by mass of flow modifier modified polyethylene wax, 1.6 parts by mass of light stabilizer 2-hydroxy-4-n-octyloxybenzophenone, 125 parts by mass of sulfur-containing olefin elastomer base material, and 0.3 parts by mass of a composite antioxidant formed by antioxidant 1010 and antioxidant 626 in a mass ratio of 1:1.5 are obtained.
[0172] The limiting oxygen index (LOI) of the obtained sulfur-containing olefin elastomer composition was 24.
[0173] Comparative Example 3
[0174] The difference from Example 8 is that the added amount of pentaerythritol is increased from 9 parts by mass to 16 parts by mass.
[0175] (1) Preparation of modified bentonite:
[0176] A plasma reactor was used, oxygen was used as a processing gas, the reaction power was 75 watts, the processing time was 45 minutes, and the gas flow rate was 45 ml / minute to modify the bentonite to obtain modified bentonite.
[0177] (2) Compounding of modified bentonite and other flame retardants:
[0178] 12 parts by mass of the modified bentonite obtained in step (1) are mixed with 12 parts by mass of hydroxyapatite, 8 parts by mass of melamine, 16 parts by mass of pentaerythritol, and 0.7 parts by mass of an aluminate coupling agent, isopropyl distearate acyloxyaluminate, to obtain a composite flame retardant material matrix.
[0179] (3) Blending of compounded flame retardant material matrix and sulfur-containing olefin elastomer:
[0180] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 225° C. for granulation, and 5.5 parts by mass of flow modifier modified polyethylene wax, 1.6 parts by mass of light stabilizer 2-hydroxy-4-n-octyloxybenzophenone, 125 parts by mass of sulfur-containing olefin elastomer base material, and 0.3 parts by mass of a composite antioxidant formed by antioxidant 1010 and antioxidant 626 in a mass ratio of 1:1.5 are obtained.
[0181] The limiting oxygen index (LOI) of the obtained sulfur-containing olefin elastomer composition was 24.
[0182] Comparative Example 4
[0183] The difference from Example 8 is that the added amount of melamine is increased from 8 parts by mass to 15 parts by mass.
[0184] (1) Preparation of modified bentonite:
[0185] A plasma reactor was used, oxygen was used as a processing gas, the reaction power was 75 watts, the processing time was 45 minutes, and the gas flow rate was 45 ml / minute to modify the bentonite to obtain modified bentonite.
[0186] (2) Compounding of modified bentonite and other flame retardants:
[0187] 12 parts by mass of the modified bentonite obtained in step (1) are mixed with 12 parts by mass of hydroxyapatite, 15 parts by mass of melamine, 9 parts by mass of pentaerythritol, and 0.7 parts by mass of an aluminate coupling agent, isopropyl distearate acyloxyaluminate, to obtain a composite flame retardant material matrix.
[0188] (3) Blending of compounded flame retardant material matrix and sulfur-containing olefin elastomer:
[0189] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 225° C. for granulation, and 5.5 parts by mass of flow modifier modified polyethylene wax, 1.6 parts by mass of light stabilizer 2-hydroxy-4-n-octyloxybenzophenone, 125 parts by mass of sulfur-containing olefin elastomer base material, and 0.3 parts by mass of a composite antioxidant formed by antioxidant 1010 and antioxidant 626 in a mass ratio of 1:1.5 are obtained.
[0190] The limiting oxygen index (LOI) of the obtained sulfur-containing olefin elastomer composition was 23.
[0191] Comparative Example 5
[0192] The difference from Example 8 is that the modified bentonite is replaced by bentonite, and the bentonite does not undergo a modification process.
[0193] (1) Compounding of bentonite and other flame retardants:
[0194] 12 parts by mass of bentonite, 12 parts by mass of hydroxyapatite, 8 parts by mass of melamine, 9 parts by mass of pentaerythritol, and 0.7 parts by mass of an aluminate coupling agent, isopropyl distearate acyloxyaluminate, are mixed to obtain a composite flame retardant material matrix.
[0195] (2) Blending of compounded flame retardant material matrix and sulfur-containing olefin elastomer:
[0196] The composite flame retardant material matrix obtained in step (1) and 5.5 parts by mass of flow modifier modified polyethylene wax, 1.6 parts by mass of light stabilizer benzophenone 2-hydroxy-4-octyloxybenzophenone, 125 parts by mass of sulfur-containing olefin elastomer base material, and 0.3 parts by mass of a composite antioxidant formed by antioxidant 1010 and antioxidant 626 in a mass ratio of 1:1.5 are added into a twin-screw extruder at 225° C. for granulation to obtain a sulfur-containing olefin elastomer composition.
[0197] The limiting oxygen index (LOI) of the obtained sulfur-containing olefin elastomer composition was 23.
[0198] Comparative Example 6
[0199] The difference from Example 8 is that the bentonite is modified by using hexadecyltrimethylammonium bromide and caprolactam.
[0200] (1) Preparation of modified bentonite:
[0201] 7 g of bentonite was added into 350 mL of deionized water to form a suspension, and hexadecyltrimethylammonium bromide and caprolactam were sequentially added into the bentonite in a mass ratio of 1:2, mixed, and dried to obtain modified bentonite.
[0202] (2) Compounding of modified bentonite and other flame retardants:
[0203] 12 parts by mass of the modified bentonite obtained in step (1) are mixed with 12 parts by mass of hydroxyapatite, 8 parts by mass of melamine, 9 parts by mass of pentaerythritol, and 0.7 parts by mass of an aluminate coupling agent, isopropyl distearate acyloxyaluminate, to obtain a composite flame retardant material matrix.
[0204] (3) Blending of compounded flame retardant material matrix and sulfur-containing olefin elastomer:
[0205] The composite flame retardant material matrix obtained in step (2) is added into a twin-screw extruder at 225° C. for granulation, and a sulfur-containing olefin elastomer composition is obtained by adding 5.5 parts by mass of a flow modifier modified polyethylene wax, 1.6 parts by mass of a light stabilizer benzophenone 2-hydroxy-4-n-octyloxybenzophenone, 125 parts by mass of a sulfur-containing olefin elastomer base material, and 0.3 parts by mass of a composite antioxidant formed by an antioxidant 1010 and an antioxidant 626 in a mass ratio of 1:1.5.
[0206] The limiting oxygen index (LOI) of the obtained sulfur-containing olefin elastomer composition was 24.
[0207] It can be seen from the results of the embodiments and comparative examples that the sulfur-containing olefin elastomer composition obtained by compounding hydroxyapatite, modified bentonite, pentaerythritol, melamine cyanurate / modified melamine cyanurate / melamine, a coupling agent, a flow modifier, a light stabilizer, and a sulfur-containing olefin elastomer base material has better flame retardant properties. In addition, it can be seen from the results of Example 8 and Comparative Examples 1-2 that the flame retardant properties of the sulfur-containing olefin elastomer composition will be reduced without adding melamine or pentaerythritol, which can confirm that the components of the present invention play a synergistic role; it can be seen from the results of Example 8 and Comparative Examples 3-4 that the amount of each component added will affect the flame retardant properties of the sulfur-containing olefin elastomer composition, and the sulfur-containing olefin elastomer composition obtained within the addition amount range of the present invention has better flame retardant properties; it can be seen from the results of Example 8 and Comparative Example 5 that if bentonite is used directly without modification, the flame retardant properties of the sulfur-containing olefin elastomer composition will be greatly reduced; it can be seen from the results of Example 8 and Comparative Example 6 that the flame retardant properties of the sulfur-containing olefin elastomer composition obtained by modifying bentonite with plasma are better than those by modifying bentonite with hexadecyltrimethylammonium bromide and caprolactam. This is because the surface of the modified bentonite is rich in active groups such as hydroxyl and carbonyl groups through plasma modification, which is beneficial to the subsequent formation of the sulfur-containing olefin elastomer composition and improves the flame retardant properties of the sulfur-containing olefin elastomer composition.
[0208] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.
Claims
1. A sulfur-containing olefin elastomer composition, characterized in that: The invention comprises the following components in parts by mass: 10-15 parts of hydroxyapatite, 11-18 parts of modified bentonite, 3-11 parts of pentaerythritol, 8-12 parts of at least one of melamine cyanurate, modified melamine cyanurate and melamine, 0.5-1 parts of coupling agent, 1-5.5 parts of flow modifier, 0.5-3 parts of light stabilizer and 90-140 parts of sulfur-containing olefin elastomer base material.
2. The sulfur-containing olefin elastomer composition according to claim 1, characterized in that The sulfur-containing olefin elastomer composition comprises: 10-11 parts of hydroxyapatite, 11-13 parts of modified bentonite, 7-9 parts of pentaerythritol, 10-12 parts of at least one of melamine cyanurate, modified melamine cyanurate and melamine, 0.7-0.9 parts of coupling agent, 1-3.5 parts of flow modifier, 0.8-2 parts of light stabilizer and 100-130 parts of sulfur-containing olefin elastomer base material.
3. The sulfur-containing olefin elastomer composition according to claim 1, characterized in that The modified bentonite is bentonite that has been subjected to plasma modification treatment.
4. The sulfur-containing olefin elastomer composition according to claim 3, characterized in that The modified bentonite is prepared by the following steps: adding bentonite into a plasma reactor, inputting a treatment gas, and treating the bentonite by utilizing electrons, free radicals, ions, and molecules in an excited state in the plasma reactor to obtain the modified bentonite.
5. The sulfur-containing olefin elastomer composition according to claim 4, characterized in that The processing gas is at least one of oxygen, nitrogen, argon and methane.
6. The sulfur-containing olefin elastomer composition according to claim 4, characterized in that The power of the plasma reactor is 30-100 watts, the processing time is 10-50 minutes, and the flow rate of the processing gas is 20-60 ml / minute.
7. The sulfur-containing olefin elastomer composition according to claim 1, characterized in that The coupling agent is one of silane, titanate and aluminate.
8. The sulfur-containing olefin elastomer composition according to claim 1, characterized in that The flow improver is at least one of polyethylene wax, low-density polyethylene, and modified polyethylene wax.
9. The sulfur-containing olefin elastomer composition according to claim 1, characterized in that: The light stabilizer is at least one of a benzotriazole light stabilizer, a benzophenone light stabilizer, and a triazine light stabilizer.
10. The sulfur-containing olefin elastomer composition according to claim 1, characterized in that The invention also comprises an antioxidant, wherein the antioxidant is added in an amount of 0.1 to 3 parts by weight.
11. The sulfur-containing olefin elastomer composition according to claim 10, characterized in that The antioxidant is selected from antioxidant 1010, antioxidant 1076, antioxidant 168, antioxidant 626 and compound antioxidants thereof.
12. The sulfur-containing olefin elastomer composition according to claim 11, characterized in that The antioxidant is a composite antioxidant, wherein the main antioxidant of the composite antioxidant is antioxidant 1010 or antioxidant 1076, and the auxiliary antioxidant is antioxidant 168 or antioxidant 626; wherein the mass ratio of the main antioxidant to the auxiliary antioxidant is 1:1-1:
2.
13. A method for preparing the sulfur-containing olefin elastomer composition according to any one of claims 1 to 12, characterized in that: The following steps are involved: Step 1: mixing hydroxyapatite, modified bentonite, pentaerythritol, at least one of melamine cyanurate, modified melamine cyanurate, melamine, and a coupling agent to obtain a composite flame retardant material matrix; Step 2: Add the compounded flame retardant material matrix, flow modifier, light stabilizer, and sulfur-containing olefin elastomer material base into an extruder for mixing, and obtain the sulfur-containing olefin elastomer composition after extrusion.
Citation Information
Patent Citations
Intumescent flame retardant polyethylene containing organosilicon compound
CN101948581A
Low-smoke halogen-free flame-retardant thermoplastic polyester elastomer and preparation method thereof
CN102757622A
Modified lignin intumescent flame retardant TPO composite material as well as preparation method and application of composite material
CN103834107A
A kind of flame retardant and its application and flame retardant polyurethane foam and its preparation method
CN106589458B
Composite modified melamine cyanurate fire retardant and preparation method and application of fire retardant
CN106700130A